Bridging the knowledge divide between public and experts using PGIS for land use planning in Malaysia. (June 2017) - Zolkafli, Amirulikhsan; Liu, Yan; Brown, Greg
Abstract: Ineffective public participation in land-use planning contributes to the lack of communication and understanding between the public and experts, acting as a barrier to successful planning outcomes. In this study, we assess whether Participatory GIS (PGIS) is a suitable method to bridge the communication gap between the public and expert knowledge for planning in the developing country context of Malaysia. Through a mixed methods approach, we investigate whether expert knowledge converges or diverges with the public's perceived knowledge obtained through a PGIS process and assess the potential benefits of PGIS from public and expert planning perspectives. The results indicate more convergence than divergence in knowledge and perspective, indicating that a PGIS process can communicate local knowledge to planning authorities to inform land use and development planning in Malaysia. Both the public and planning experts recognize the potential benefits of PGIS, but successful implementation will require major changes in traditional Malaysian public participation processes. Highlights: We assessed if PGIS is suitable to bridge the communication gap between public and expert in developing country context. More convergence than divergence exists in knowledge obtained between expert and public through the PGIS process. PGIS process can communicate local knowledge to planning authority to inform land-use and development planning in Malaysia. Successful PGIS implementation will require major changes in traditional Malaysian public participation processes.